Life Expectancy and Life Years Lost After HIV Diagnosis in Puerto Rico, 2000-2020 - Burgos-Barreto, Grisel; Reyes, Daniel; Tremblay, Raymond L (British Journal of Healthcare and Medical Research, 2024)
Background: In 2019, the Global Burden of Disease estimated that HIV/AIDS was globally the second top cause for disability-adjusted life years in individuals 25–49 years of age and the ninth most common cause for young individuals between the ages of 10-24. The objective of this study was to estimate the average life expectancy and life years lost (LYL) in individuals diagnosed with HIV in Puerto Rico from 2000-2020 and to evaluate the relationship between LYL and demographic factors. Methods: The epidemiological design was a retrospective cohort study of 11,524 people diagnosed with HIV who received services under the Eligible Metropolitan Area (EMA) of San Juan, Puerto Rico. The population among this cohort was described using socioeconomic characteristics with frequencies and proportions by category. We estimated the LYL by matching the expected residual lifetime for someone diagnosed with the disease with the life expectancy of the general population at that specific age as the null model. Results: LYL is greater with earlier HIV onset and is also influenced by level of poverty, type of insurance, and documented mode of transmission of HIV. The average life expectancy (number of years alive remaining after diagnosis) across all ages of an HIV-diagnosed individual is between 12 and 14 years. We found greater LYL in HIV patients with lower income status across age groups; in those without insurance, significantly in ages of 40-49 years; as well as with perinatal transmission versus other modes of transmission, and intravenous drug use versus heterosexual contact. No distinction was found between males versus females. Conclusion: This study reaffirms the importance of prevention and demographic aspects such as age, poverty level, insurance type, and factors related to lifestyle (transmission modes) to develop better prevention strategies to reduce the LYL as a consequence of HIV.